Impact of Governance and Social Development on Fiscal Deficit in Pakistan (Journal of Asian Development Studies, 2019)
This short empirical study is about to determine the implications of Governance and social development on Fiscal deficit of Pakistan by using time series data for the period of 1980 to 2014. The study is dynamic in nature with compare to previous literature on the determinants side of fiscal deficit the study incorporated education index and life expectancy as social development indicators and corruption index with Government stability for governance indicators. For empirical estimation the study firstly applies a unit root test to check order of integration then a Johansson test of Co-integration is applied. Study found that all the indicators used in the model are co-integrated of I(1) so as per rule for long run relationship VECM is used. The main findings of this empirical study are that, corruption and government stability are found significant measures for fiscal deficit and education index is also significantly contributor in fiscal consolidation of the Pakistan. Technically the study has sound contribution in the literature of fiscal deficit particularly in case of developing countries like Pakistan where social as well as governance indicators are shown poor situation and helpful for further research on the same subject.